Development and Validation of Alternative Palm-Derived Substrates for Seedling Production - María Pilar Gomis; María Dolores Pérez-Murcia; Xavier Barber; Encarnación Martínez-Sabater; Raúl Moral; María Ángeles Bustamante (Agronomy, 2022)
The constraints associated with peat use in horticulture has led to a search for alternative materials for their use as growing media. The organic materials derived from palm trees (composted or not) can constitute an alternative due to their ligneous and fibrous character, similar to coir fiber. This work studies the feasibility of using several palm-tree-derived (Phoenix dactylifera L.) organic materials as growing media ingredients for the transplant production of lettuce (Lactuca sativa L. var. Senna). For this, the following substrates were studied: five mixtures for each palm-derived material (palm trunks and leaves and composts derived from palm trunk and leaves), in the proportions of 20%, 40%, 60%, 80%, and 100% by volume, mixed with coir fiber. Coir fiber at the proportion 100% was used as the control treatment. Physical, physico-chemical, and chemical analyses were conducted on the substrates, and the germination and morphological parameters of the seedlings were examined. Chemometric tools, such as random forest (RF) and hierarchical cluster analysis (HCA) were also used to evaluate the data obtained. The type and proportion of material used in the growing media principally affected the parameters studied in the lettuce seedlings. The substrates with a percentage of compost lower than 60% showed behavior closer to that observed in the growing media with 100% coir fiber and with the mixture of coir fiber and palm leaves or trunks at all proportions.